Canning of shrimps (Penaeus marquiensis) in buffered brine - Mayor, Rosalinda S.
This study was undertaken to determine effective treatments and procedures for the production of commercially acceptable canned shrimps. Different packing media were used to assess their efficiency in preventing shrimp discoloration. Frozen and pre-treated shrimps; sulfited and chlorinated prior to freezing, were also tested for their suitability for canning. Adequacy of two canning procedures was evaluated through heat penetration studies. Objective and subjective examinations were done to determine effects of treatments and procedures used. The most effective packing medium for the prevention of discoloration in canned shrimps was found to be citric acid buffer. This contained 0.25% citric acid and 2% salt. Frozen and pre-treated shrimps were likewise found to be fit for canning as the fresh raw material. Despite one week of frozen storage at 15.6°F, no undesirable quality changes were observed in treated and untreated samples. Sulfite pre-treatment was found relatively more efficient than chlorination in inhibiting deteriorative changes during frozen storage. The processing procedure found adequate for shrimps packed in 307 x 201 1F C-enamel cans entails processing for 15 minutes at 250°F. Texture alterations were however noted in samples processed in this manner.